Mechanical witness a history of motion picture evidence in U.S. courts - Schwartz, Louis Georges (New York ; Oxford : Oxford University Press, 2009)
This title charts the changing role and theoretical implications of the use of film and video as courtroom evidence. The author moves from the earliest uses of film in courts to Bin Laden's taped statements after 9/11, revealing how the courts have developed a reliance on film and video technologies.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Video tapes in courtroom proceedings -- United States; Motion pictures -- Law and legislation -- United States; Evidence, Documentary -- United States; Courts -- United States; Judicial process -- United States